1989
DOI: 10.1095/biolreprod40.2.379
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructu rat Observations of Human and Mouse Oocytes Treated with Cryopreservatives1

Abstract: The effects of the cryopreservative agents dimethylsulfoxide (DMSO) and propanediol (PROH) on mature human and mature mouse oocytes have been examined with transmission electron microscopy. Treatment of CD-1 mouse oocytes and human preovulatory oocytes in a stepwise manner with either DMSO or PROH up to 1.5 M appears to trigger the exocytosis of 70-80% of the cortical granules in all oocytes. Successive stages in premature dehiscence, including a loss in granule electron density, fusion of the granule-limiting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
41
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(47 citation statements)
references
References 49 publications
5
41
1
Order By: Relevance
“…Rather consistently, the presence of vacuoles was described by our group as well as by others in association with a variety of CRSC protocols [19,23,36]. It is tempting to hypothesize that vacuoles located peripherally may evolve from crypt-like invaginations and clusters of endocytic vesicles which form in the oocyte cortex following simple exposure to CPA, as shown by Schalkoff et al [41]. However if this assumption is correct, it remains to be explained why oocytes vitrified through the cryoleaf method, which are exposed to high concentrations of CPAs, do not exhibit an increase in the number of vacuoles, as we recently reported [39].…”
Section: Discussionsupporting
confidence: 61%
“…Rather consistently, the presence of vacuoles was described by our group as well as by others in association with a variety of CRSC protocols [19,23,36]. It is tempting to hypothesize that vacuoles located peripherally may evolve from crypt-like invaginations and clusters of endocytic vesicles which form in the oocyte cortex following simple exposure to CPA, as shown by Schalkoff et al [41]. However if this assumption is correct, it remains to be explained why oocytes vitrified through the cryoleaf method, which are exposed to high concentrations of CPAs, do not exhibit an increase in the number of vacuoles, as we recently reported [39].…”
Section: Discussionsupporting
confidence: 61%
“…Another unavoidable drawback of the vitrification and warming process affecting oocytes, independently from the used device, is premature exocytosis by cortical granules and subsequent ZP ''hardening,'' as previously shown after cryoprotection with DMSO (18,48). Consistently, electron-dense and electron-lucent granules, swollen SER vesicles, and severely altered mitochondria very difficult.…”
Section: Discussionmentioning
confidence: 92%
“…It has been demonstrated that frozenthawed mouse oocytes have a reduced in vitro fertilization (IVF) rate due to changes (hardening) in the zona pellucida blocking sperm penetration (Carroll et al, 19901, and that these changes are mediated by premature release of cortical granules (CG) (Vincent et al, 0 1995 WILEY-LISS, INC. 1990). Schalkoff et al (1989) also found that exposure of mature mouse and human oocytes to cryoprotectants such as DMSO and propanediol prior to freezing causes a significant premature exocytosis of CG. The phenomenon has not been studied in the bovine.…”
Section: Introductionmentioning
confidence: 87%